The hippocampus and spatial constraints on mental imagery - Bird, Chris M.; Bisby, James A.; Burgess, Neil (Frontiers in Human Neuroscience, 2012)
We review a model of imagery and memory retrieval based on allocentric spatial representation by place cells and boundary vector cells in the medial temporal lobe, and their translation into egocentric images in retrosplenial and parietal areas. In this model the activity of place cells constrain the contents of imagery and retrieval to be coherent and consistent with the subject occupying a single location, while the activity of head-direction cells along Papez’s circuit determine the viewpoint direction for which the egocentric image is generated. An extension of this model is discussed in which a role for grid cells in dynamic updating of representations (mental navigation) is included. We also discuss the extension of this model to implement a version of the dual representation theory of post-traumatic stress disorder (PTSD) in which PTSD arises from an imbalance between weak allocentric hippocampal-mediated contextual representations and strong affective/sensory representations. The implications of these models for behavioural, neuropsychological and neuroimaging data in humans are explored.